The appropriation of knowledge from artistic expression. - Castro Bonilla, Julieta (2011)
In this article we examine and expose some of the results of a research work based on the appropriation of knowledge through visual expression, activity attended by teachers and students outside the schooleducational method called "Open Classroom".After the investigation, it is evident that thestudy, inquiry, reflection and the searchsystematic knowledge and ways of learning andteach the teacher, are key elements that promote qualitative changes in thethis academic training, which allows youthe classroom in innovative ways to achieve significant learning in their students. The design of learning situations from a constructivist perspective, holistic and playful, and the use of contexts, allowed the achievement of learning cognitive, affective and psychomotor throughexpression of artistic activities, enabling itthe young developing an integrated personality